علم قراءات کی تدوین و ارتقاء(قراءات کے ضوابط کے تناظر میں) - ڈاکٹر قاری تاج افسر (FIKR-O NAZAR فکر ونظر, 2011)
The Science of recitation was initially limited to pedagogy only. As per their capacity Sahaaba-i-kiram (razi Allah o anhum) used to note down the holy verses and their explanation pronounced by the Holy Prophet. But because of their far off journeys and gradual revelation of the Holy Quran, complete compilation could not be materialized. The first caliph Hazrat Abubakr compiled the Holy Quran. When the process of compilation of the related sciences and formation of the relevant rules started taking shape during the period of taabieen, the foremost science was that of Qira'at as it was related to the text of the Holy Quran. So its compilation started before 90 H. How did the science of Qira'at develop through different phases of history? In how many way did the scholars of the Ummah contribute to it to bring it to culmination? What are the differences among various phases as per compilation? What are the criteria for judgment of a Qira'at? How were the Harf-i-Sab'ah transformed into Qira'at-i-Sab'ah? How did the number of these Qira'at rise from seven to twenty? How can wejuxtapose Qira'aat-i-Sab'ah with Qira'at-i-Salasah to determine the status of the latter. These are the points to be explored in this paper. The development has been divided into four stages.